Pengaruh Model Storytelling terhadap Kemampuan Menyimak Cerita Bergambar pada Siswa Kelas V MIS Insan Ikhlas Islamic School Medan - Rahma Dita; Sapri Sapri; Lailatun Nur Kamalia Siregar (Jurnal Bintang Pendidikan Indonesia, 2024)
This research is motivated by low learning outcomes and teachers have not used appropriate models in the learning process. The aim of this research is to find out the influence of the Storytelling learning model on the ability to listen to illustrated stories in Class V at MIS Insan Ikhlas Islamic School. The population in this study was 65 students. With a sample of class V A as the experimental class totaling 34 students and class V B as the control class totaling 31 students. Sampling used total sampling. To analyze the data, the Independent sample t-test was used using SPSS version 20. The results obtained after using the Storytelling learning model, namely the experimental class, obtained an average score of 84.4. Students' Listening Ability is assessed in the very Good category. There is an influence of the Storytelling learning model on the ability to listen to picture stories in Class V with the results of the calculated t test showing that at a significant level of 5%, the calculated value shows a tcount value of 4,646. Meanwhile for ttable at N = 65, namely 1.668. So tcount 4,646 > ttable 1,668.